Antiprocesalism in the Colombian Legal System - Bejarano Ricaurte, Ana (2019)
Since the beginning of the 20th century the Colombian legal system has displayed a theory called ‘antiprocesalism’, according to which judges are not bound by their own decisions if they are so mistaken, so they can be considered as illegal. When this happens, judges can ignore those decisions. There is currently no consensus regarding the practical application of this theory, whether the judge can automatically ignore its own decisions, or whether the mistake must be pointed out by the parties. There is also discussion regarding when can those decisions be ignored related to their enforceability and if this theory can be applied to any type of judicial decision. This uncertainty has produced the irregular application of this theory, sometimes even damaging the right to due process, specially coming from lowercircuit judges. Still, current and past decisions from the nation’s highest courts present some viable criteria for the safe and uniform application of this theory in legal practice. Those criteria are studied and presented in this essay.